Loot boxes, problem gambling and problem video gaming: A systematic review and meta-synthesis. (April 2022) - Spicer, Stuart Gordon; Nicklin, Laura Louise; Uther, Maria; Lloyd, Joanne; Lloyd, Helen; Close, James
Loot boxes (LBs) are video game-related purchases with a chance-based outcome. Due to similarities with gambling, they have come under increasing scrutiny from media, academics and policymakers alike. Initial evidence suggested that LB engagement might be associated with both problem gambling (PG) and problem video gaming (PVG). We therefore conducted a systematic review of the evidence for associations between LB purchasing, PG and PVG. For LB/PG, 12 of 13 publications reported a positive relationship, with a moderately sized mean effect of r = .27. For LB/PVG, the mean effect was r = .40, although this finding was drawn from only six surveys in total. For PG/PVG, the mean effect was r = .21, with only 11 of 20 studies reporting significant effects. While further evidence is required to determine the direction of causality, the strength of relationships suggests that policy action on LBs may have benefits for harm minimisation.